PERAN GURU DALAM PENGEMBANGAN KARAKTER SISWA UNTUK MENJAGA KEUTUHAN DAN KEMAJUAN BANGSA INDONESIA - I Wayan Suastra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The integrity and progress of the Indonesian nation is determined by the strength ofcharacter education of its human resources. Character education for students needs to becontinuously developed, whether at home, community, or school. In school, the role of the teacheris very important to build the character of the students. Teachers must be professional and alsocharacter of Indonesia, namely: mastering in depth the field being taught, understanding thecharacter of learners including local culture, always innovate in learning, teach learning howto learn, master IT and have networking, appreciate the diversity , tolerant, guarding the fourpillars of nationality, become role models for their students and apply the system among KiHajar Dewantara ing ngarsa sung tuladha, ing madya mangun karsa, and tut wuri handayani.